From Public–Private Virtue to Cultural-Corporate Amoeba: Mr Blobby and the Rise of BBC Worldwide During the 1990s. Issue 2 (3rd April 2018) - Jacobs, Jason; Thomas, Deborah J.
Abstract : In 1991, a BBC taskforce inquired into the organization's efficiency. One of its reports, BBC the Entrepreneur, observed that 'commerce is no longer incompatible with the BBC's core businesses' and that, 'entrepreneurialism was a requirement of the 1980s and will still have an important part to play in the public sector in the 1990s. The BBC's involvement in commerce signals that it is a part of the market.' In fact, the BBC had participated in the market since the 1950s, running co-productions, selling merchandise and publications, exploiting its archive, and sponsoring exhibitions, although these activities were constrained by an overwhelming institutional sense of the virtues of public service broadcasting. However, by the 1990s, as this report indicated, there was a radical shift towards welcoming commercial values as a means to underpin and stimulate entrepreneurial behaviour. This article tracks the career of Mr Blobby, a humorous character featured on the variety show Noel's House Party (1991–1998) as representative of this shift. We argue that, while Mr Blobby was frequently read as an emblem of simple-minded commercial degradation, he also represented a transitional and generative development in the evolution of the solid corporate metabolism of BBC Worldwide of the present day.